ENVIRONMENTAL DEGRADATION AND CONSERVATION IN THE CROSS RIVER AREA: A HISTORICAL APPRAISAL OF COLONIAL AND POST COLONIAL INTERVENTIONS - Offiong, Ekwutosi Essien (PEOPLE: International Journal of Social Sciences, 2016)
Environmental degradation in Africa has been a recurring decimal due to lack of awareness, harmful traditional practices and other forms of neglects. The Cross River Area of Nigeria has suffered all of these problems. Covering a land mass from the mangrove and fresh water swap on the coast through the tropical rain forest to the grassland on its northern fringes, the region contains one of the largest surviving tropical rain forests, South of the Sahara. These forests serve as habitat for rare species of several flora and fauna. Over the years, these forests have been persistently degraded by the inhabitants of the region through felling of trees in the mangrove swamp for firewood, cutting of trees in the rain forest for timber and firewood, bush burning for farming, poaching of animals and other industrial activities, all these activities constitute problems to the environment. There have been several awareness campaigns by international organizations, national bodies and local groups to conserve the environment and stem the tide of this degradation. These campaigns have to some extent controlled the spate of degradation but the problems already created are evident within the environment. This paper would examine environmental degradation in the region and the activities of national and international organizations to combat this menace and conserve the environment in the Colonial and Post-Colonial period. The methodology adopted here is inter-disciplinary approach making use of several available literature on the subject matter. It was discovered that Government and non-governmental agencies over the years have been intervening in a bid to curb environmental degradation. However, these interventions have not yielded the much needed results envisaged.